2020
DOI: 10.1111/jgs.16443
|View full text |Cite
|
Sign up to set email alerts
|

Action at a Distance: Geriatric Research during a Pandemic

Abstract: BACKGROUND “Action at a distance” may be the new norm for clinical researchers in the context of the COVID‐19 pandemic that may require social distancing for the next 18 months. We must minimize face‐to‐face contact with vulnerable populations. But we must also persist, adapt, and help our older patients and study participants during the pandemic. METHODS Clinical researchers have an obligation to help, and we can. Recommendations for clinical researchers working with older adults during the COVID‐19 pandemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
129
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(132 citation statements)
references
References 22 publications
0
129
0
3
Order By: Relevance
“…This pandemic also threatens the -patients of tomorrow.‖ Researchers have already sounded the alarm on how the COVID-19 pandemic may affect clinical research in unprecedented ways. 33,34 The consequences may be even more dire for ADRD research. Over the past two decades, ADRD has become one of the most active areas of both basic and clinical research, attracting major industry, government, and philanthropic funding in the Western world.…”
Section: (6) Covid-19 Potential Impact On Adrd Research Threatens Thementioning
confidence: 99%
See 2 more Smart Citations
“…This pandemic also threatens the -patients of tomorrow.‖ Researchers have already sounded the alarm on how the COVID-19 pandemic may affect clinical research in unprecedented ways. 33,34 The consequences may be even more dire for ADRD research. Over the past two decades, ADRD has become one of the most active areas of both basic and clinical research, attracting major industry, government, and philanthropic funding in the Western world.…”
Section: (6) Covid-19 Potential Impact On Adrd Research Threatens Thementioning
confidence: 99%
“…35 Abrupt interruption of all these research studies would not only jeopardize a crucial investment society has already made, but it could also have long lasting consequences for the field of ADRD research. At the same time, the COVID-19 pandemic could be a welcome catalyst to accelerate the adoption of innovative design and methods in clinical research, 33 fundamentally changing the way participants in trials for ADRD are recruited and assessed. The rest of this section discusses whether and how ADRD clinical research can continue during the pandemic.…”
Section: (6) Covid-19 Potential Impact On Adrd Research Threatens Thementioning
confidence: 99%
See 1 more Smart Citation
“…The likelihood is that COVID-19 will become endemic, which suggests long-term behavioural adjustments as reported in our study [45]. Similarly, we argued that social distancing is not part of the culture in either developed or developing countries, for different reasons [60]. In developing countries, it is more related to population density, crowding, workplace conditions etc., such as overcrowding in public transport.…”
Section: Discussionmentioning
confidence: 49%
“…36 Rahmel at al showed that patients surviving sepsis had a better 5-year survival when bene ting from a rehabilitation program. 37 In an RCT of 72 COVID-19 patients (median age 69), Liu et al reported that a six-week respiratory rehabilitation program could improve pulmonary function and quality of life. 38 Finally, ethical standards should facilitate inclusion of elderly adults with more adapted informed consent, including the possibility to obtain consent by proxy if the patient has diminished capacity.…”
Section: Observational Studiesmentioning
confidence: 99%